IMPROVING THE EFFICIENCY OF RAIL TRANSPORT: THE WORLD EXPERIENCE - EGAMBERDIEVA KHURSHIDAKHON ALISHEROVNA (TADQIQOTLAR, 2025)
Railroad transportation is a complex system of a country’s economy. In a situation where managing a simple system requires a special approach, a complex system such as railroad transportation must be based on well-designed and effective principles for the entire country. In recent years, many countries have undergone various forms of railroad reform. The most common of these is the process of vertically integrated liberalization. This article examines the achievements and consequences of this process in different countries. The purpose of the study is to examine changes in the global transport system as an experiment, i.e. to determine the feasibility of such processes as privatization and liberalization of rail transport in different countries on the railroads of Uzbekistan.[1] As mentioned above, when implementing reforms or changes related to the liberalization of rail transport, it is necessary to analyze its competitiveness in different countries, because any action to be taken on rail transport should ultimately improve its operational efficiency. Consequently, it is necessary to assess the importance of railroad liberalization in terms of improving the efficiency of railroad operations through indicators of competitiveness.[2]